Pemanfaatan Hidroponik sebagai Sarana Pemanfaatan Lahan Terbatas di SMP Negeri 26 Makassar - Ida Yesika Arruan; Iryuni Saskiah Idham; Nur Maulidna Devi; Valencia Putri Mariska; Sitti Rahma Yunus (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2024)
UPT SPF SMP Negeri 26 Makassar is one of the Junior High Schools located at Jalan Traktor 6, No. 21, Mangasa, Kec. Tamalate, Makassar City, South Sulawesi. The purpose of this service program is to equip students with activities that foster an entrepreneurial spirit at school. The implementation of this service took place at UPT SPF SMPN 26 MAKASSAR, Mangasa, Tamalate. This activity lasted for 1 month starting April 30, 2024 until May 31, 2024. The target audience of the activity is teachers and students of SMPN 26 Makassar. The method used in this activity is to conduct lectures to students, namely providing knowledge and understanding of how to grow hydroponic systems along with their benefits and advantages. Through the making of hydroponics can stabilize the school community, especially in the field of plant cultivation on narrow and limited land.